1998
DOI: 10.2165/00003088-199835050-00002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics of Diacerein

Abstract: Diacerein is a drug for the treatment of patients with osteoarthritis. This drug is administered orally as 50 mg twice daily. Diacerein is entirely converted into rhein before reaching the systemic circulation. Rhein itself is either eliminated by the renal route (20%) or conjugated in the liver to rhein glucuronide (60%) and rhein sulfate (20%); these metabolites are mainly eliminated by the kidney. The pharmacokinetics characteristics of diacerein are about the same in young healthy volunteers and elderly pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(66 citation statements)
references
References 18 publications
3
62
0
1
Order By: Relevance
“…47 It was noticed that all permeated drug was measured as rhein, which agreed with previous reports that DCN is completely converted into rhein before reaching the circulation. 48 As shown in Figure 5, the cumulative amounts permeated after 120 minutes were 450.48±10.51, 108.28±1.06, and 97.83±6.53 µg for DNS-F7, CS-DNS-F10, and DCN suspension, respectively. Although there are too many reports suggesting that CS has a permeation enhancement effect 21 either θ Figure 4 Powder X-ray powder diffraction (A) and scanning electron microscopy (B) of DNs-F7 and cs-DNs-F10.…”
Section: Ex Vivo Permeationmentioning
confidence: 82%
“…47 It was noticed that all permeated drug was measured as rhein, which agreed with previous reports that DCN is completely converted into rhein before reaching the circulation. 48 As shown in Figure 5, the cumulative amounts permeated after 120 minutes were 450.48±10.51, 108.28±1.06, and 97.83±6.53 µg for DNS-F7, CS-DNS-F10, and DCN suspension, respectively. Although there are too many reports suggesting that CS has a permeation enhancement effect 21 either θ Figure 4 Powder X-ray powder diffraction (A) and scanning electron microscopy (B) of DNs-F7 and cs-DNs-F10.…”
Section: Ex Vivo Permeationmentioning
confidence: 82%
“…Patients treated with SAMe had complaints of mild gastritis. The major AE reported with diacerein was discoloration of urine, due to the elimination of its metabolites via the kidney, which is of no clinical significance [24]. Although the incidence of diarrhoea was higher in the diacerein group, the event may be considered more as patient discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…In a cartilage explant model, it was found that diacerein and rhein could reduce the levels of caspase-3 and iNOS [12] . Previous studies have reported that diacerein is safer than non-steroidal anti-inflammatory drugs [1,13,14] . Moreover, it can even be used in cases of renal and liver impairment [14] .…”
Section: Introductionmentioning
confidence: 96%